Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/cancers12113328
|View full text |Cite
|
Sign up to set email alerts
|

Trop2: Jack of All Trades, Master of None

Abstract: Trophoblast cell surface antigen 2 (Trop2) is a widely expressed glycoprotein and an epithelial cell adhesion molecule (EpCAM) family member. Although initially identified as a transmembrane protein, other subcellular localizations and processed forms were described. Its congenital mutations cause a gelatinous drop-like corneal dystrophy, a disease characterized by loss of barrier function in corneal epithelial cells. Trop2 is considered a stem cell marker and its expression associates with regenerative capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 179 publications
(248 reference statements)
2
54
0
Order By: Relevance
“…Trophoblast cell surface antigen 2 (TROP2) is a 36 kDa transmembrane glycoprotein, highly expressed on several types of solid cancer ( Cubas et al, 2009 ; Zeng et al, 2016 ). It is also considered a stem cell marker ( Lenárt et al, 2020 ). Hou J. et al (2019) demonstrated high TROP2 expression on GBM cells from surgically removed patient tumors compared to low levels on normal brain cells.…”
Section: Targets Of Car T Cell Therapy In Preclinical Studiesmentioning
confidence: 99%
“…Trophoblast cell surface antigen 2 (TROP2) is a 36 kDa transmembrane glycoprotein, highly expressed on several types of solid cancer ( Cubas et al, 2009 ; Zeng et al, 2016 ). It is also considered a stem cell marker ( Lenárt et al, 2020 ). Hou J. et al (2019) demonstrated high TROP2 expression on GBM cells from surgically removed patient tumors compared to low levels on normal brain cells.…”
Section: Targets Of Car T Cell Therapy In Preclinical Studiesmentioning
confidence: 99%
“…Trop2 is a 46-kDa monomeric glycoprotein that has properties such as preferential overexpression, constitutive endocytosis, and routing to lysosomes that make it a highly attractive target for ADCs. A review of Trop2 and its function in normal and diseased cells can be found in [ 119 ]. Trop2 overexpression on the cell surface is well documented, and it has been identified in approximately 30 different tumor types [ 119 ].…”
Section: Target Antigens For Approved Adcs and Their Endocytosis Characteristicsmentioning
confidence: 99%
“…A review of Trop2 and its function in normal and diseased cells can be found in [ 119 ]. Trop2 overexpression on the cell surface is well documented, and it has been identified in approximately 30 different tumor types [ 119 ]. However, Trop2 is interesting due to the amount of protein detected in the cytoplasm of tumor cells and the association with patient prognosis.…”
Section: Target Antigens For Approved Adcs and Their Endocytosis Characteristicsmentioning
confidence: 99%
“… 12 It consists of 323 amino acids 13 and has extracellular domain, short transmembrane domain and a cytoplasmic tail. 14 …”
Section: Introductionmentioning
confidence: 99%